Pengaruh Kompensasi, Kepemimpinan dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan. - Confessa, I Made Tresna Suputra Angelo; Ardana, Komang (E-Jurnal Manajemen, 2014)
The purpose of this research is to know the influence of simultaneous and partial of compensation, leadership and the work environment to the employees' job satisfaction in PT Anugrah Merta Sari Sedana Denpasar. Respondents in this study as much as 90 employees. The analysis technique used in this study is the analysis of multiple linear regression with simultaneous regression test (f test) and partial regression test (t test). Based on the analysis of the results obtained that the simultaneous and partial shows compensation, leadership, environmental conditions of work had an significant influence on job satisfaction employees at PT Anugrah Merta Sari Sedana Denpasar. Advice can be lodged is that incentives to based on a level presence and productivity work. Leaders need concerning the aspect of appreciation to work performance and discipline employees so that can be good influence to employees. Having regard to the lighting on the environment in the workplace can also affect job satisfaction at the company.